The influence of American product boycott on brand switching intention: The role of e-WOM as a moderator - Damayanti, Rizki Wahyuning; Sumayyah, Sumayyah (Department of Accounting, Faculty of Business, Universitas PGRI Yogyakarta, 2024)
This research aims to determine the influence of product boycotts on brand switching intentions with Electronic Word of Mouth (EWOM) as a moderator. This research is quantitative, with surveys as the data collection method. Data collection for this research was carried out on all Indonesian people who participated in boycotting American products such as KFC, McDonald's, Starbucks, and others. The data collection method uses an online questionnaire via Google Form, which is obtained directly from the field. Data collection is only carried out once and represents at that time or cross-sectionally. This research shows that product boycotts positively and significantly affect brand-switching intentions. Meanwhile, EWOM did not moderate the influence of the product on brand-switching intentions.